Acute neurological deficit caused by thoracic pseudomeningocele after spinal surgery - Choong Hoon Foo; Beatrix Yung Siang Hii; Chung Chek Wong; Khin Maung Ohn (BMJ Publishing Group, 2021)
Postoperative pseudomeningocele usually has a benign course. We report a rare presentation of postoperative acute neurological deficit caused by compressive thoracic pseudomeningocele. This patient had posterior spinal fusion and decompression surgery for thoracic ossification of posterior longitudinal ligament and ligamentum flavum. Intraoperative incidental durotomy was covered with hydrogel dural sealant. She developed acute neurological deterioration 1 week after index surgery. Emergency decompression surgery was performed. One year after the surgery, she showed good neurological recovery.